Analysis of the Development of Chemistry Analysis Try-Out Questions and Their Impact on the Graduation of Professional Teacher Education (PPG) Students - Anugrah Ricky Wijaya; Nur Atikah (J-PEK (Jurnal Pembelajaran Kimia), 2026)
This study describes the development of try-out questions for Professional Teacher Education (PPG) students in Chemical Analysis at Universitas Negeri Malang. The try-out questions, consisting of 35 Pedagogical Content Knowledge (PCK) questions, were designed to assess students' understanding of chemistry analysis and their ability to apply it in real-world scenarios. The development process involved integrating Question Analysis Materials, Subject Matter Study Materials, and Cognitive Level of Questions to create relevant and challenging questions. Expert feedback was incorporated to revise and improve the questions, resulting in a low error rate of 5% for the Chemical Analysis set questions. The try-out questions demonstrated promising results, with a 100% pass rate for PPG students in Chemical Analysis.